Towards universal health coverage in Zambia: impediments and opportunities. Issue 3 (2nd April 2016) - Aantjes, Carolien; Quinlan, Timothy; Bunders, Joske
ABSTRACT: Universal health coverage has been given a prominent place in the post-2015 global development agenda, but there are concerns over its feasibility in low- and middle-income countries. This article assesses successive Zambian governments' efforts to achieve this agenda. We discuss the recent restructuring of health governance to support policies that re-emphasise the social determinants of health and health equity. This includes a new Ministry of Community Development and Mother and Child Health alongside the Ministry of Health. We argue that recent innovations in policy and practice need to be extended to include ministries which focus on economic development.